The measurement reliability and equivalence of print versus online versions of the Youth Activity Profile - Yang Bai; Philip M. Dixon; Pedro F. Saint-Maurice; Paul R. Hibbing; Gabriella M. McLoughlin; Michael Pereira da Silva; Gregory J. Welk (PLoS ONE, 2025)
Purpose The Youth Activity Profile (YAP) is a 7-day self-report designed to quantify physical activity and sedentary behaviors among youth. This study evaluated the reliability of the online version of the YAP and equivalence with the paper-based version. Method A total of 2,490 participants from 17 schools in Iowa and Texas completed the YAP. Each classroom was randomly assigned to complete either the print or online version twice. A variance components model was used to assess the test-retest reliability and equivalence testing was also applied. Results Both paper and online versions had similar reliability for the PA estimates in school (ICCprint = 0.69–0.91; ICConline = 0.54–0.84), at home (ICCprint = 0.72–0.83; ICConline = 0.64–0.94), PA at weekend (ICCprint = 0.33–0.72; ICConline = 0.39–0.70), and SB (ICCprint = 0.69–0.90; ICConline = 0.66–0.80). The two versions were statistically equivalent for most YAP items except for recess. Conclusion The online YAP appears to be a reliable assessment of physical activity and sedentary behavior in youth populations.